PERAN PENYULUH DALAM TINGKAT PERKEMBANGAN KELOMPOK TANI - Bilqis Naufi; Iwan Armawan (Jurnal Kommunity Online, 2022)
This study aims to describe the characteristics of farmers, the development of farmer, the role of agricultural extention agent, and analyze the role of agricultural extension agent in the development of farmer group in Ciampea Udik District. The whole 18 members of farmers group were the respondents of the research. Data were analyzed by Statistical Package of the Social Science (SPSS). The results showed that the level of the role of agricultural extension agent in the development of farmer in Ciampea Udik District is high.